2016
DOI: 10.3892/mco.2016.855
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of enlarged lateral pelvic lymph nodes before and after preoperative chemoradiotherapy for rectal cancer

Abstract: Abstract. Preoperative chemoradiotherapy (CRT) with total mesorectal excision (TME) is the widely accepted treatment for rectal cancer (RC) in Western countries. However, there remains controversy as to whether preoperative CRT is useful in tumors that extend beyond the mesorectum, including metastasis to the lateral pelvic lymph nodes (LPLN). The aim of this study was to assess the prognostic significance of LPLN enlargement in patients with RC who receive preoperative CRT followed by TME without LPLN dissect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Patients were classified based on the long-axis diameter of the regional LN on CT images as small (≤ 7 mm; n = 118) and large (> 7 mm; n = 58) LN groups. The reference value for long-axis diameter was determined as 7 mm, because the partial volume effect is significant when the target of interest is smaller than 2 times of the PET/CT system’s full-width at half-maximum (FWHM) (< 8 mm) [ 18 ], and the long-axis diameter range on multiple detector CT has been reported as 7–10 mm for the diagnosis of metastatic regional LN [ 19 , 20 ]. This study was approved by the Institutional Review Board of our institution.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were classified based on the long-axis diameter of the regional LN on CT images as small (≤ 7 mm; n = 118) and large (> 7 mm; n = 58) LN groups. The reference value for long-axis diameter was determined as 7 mm, because the partial volume effect is significant when the target of interest is smaller than 2 times of the PET/CT system’s full-width at half-maximum (FWHM) (< 8 mm) [ 18 ], and the long-axis diameter range on multiple detector CT has been reported as 7–10 mm for the diagnosis of metastatic regional LN [ 19 , 20 ]. This study was approved by the Institutional Review Board of our institution.…”
Section: Methodsmentioning
confidence: 99%
“…While the role of nCRT for LPNM has become clearer in recent years, it is well recognized that nCRT cannot eliminate all malignant cells within LPNs. The results of this study suggest that LPNM is influenced by both post-nCRT size and the sensitivity of LPN classification [19,23,24]. Oh et al [19] reported that persistent LPNs ≥ 5 mm on post-nCRT MRI were more significantly associated with residual tumour metastasis than responsive LPNs after nCRT (61.1% vs 0%, P = 0.001), and multivariable analysis revealed post-nCRT LPN size to be a significant and independent risk factor for LPNM (OR = 2.390; 95% CI = 1.104-4.069, P = 0.001).…”
Section: Discussionmentioning
confidence: 85%
“…Yamaoka et al [23] also found that in the nCRT group, the optimal cut-off value of post-nCRT LPN size was 5 mm, with a sensitivity of 71.4% and specificity of 85.3% for positive LPNM. Inoue et al [24], however, considered a 7 mm cut-off more appropriate. In our study, we set 5 mm as the cut-off for post-nCRT LPN size.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathologic degree of tumor regression was based on the Guidelines for the Clinical and Pathologic Studies on Carcinoma of the Colorectum and was classified into 1 of the following 4 categories: grade 0, no necrosis or regressive changes; grade 1a, >⅔ vital residual tumor cells (VRTCs): grade 1b, approximately ⅓ VRTCs; grade 2, < ⅓ VRTCs; and grade 3, no VRTCs . Nonresponders were defined as patients with histopathological tumor regression grades 0–1b, and responders were defined as those with grades 2–3, as previously described …”
Section: Methodsmentioning
confidence: 99%